Perancangan dan Implementasi Sistem Pencatatan Akuntansi dengan Microsoft Access pada Sinar Bulan Bintang - Kelly Kelly; Mardianto Mardianto (Prosiding, 2023)
This study aims to design an accounting record system using Microsoft Access to overcome the constraints and deficiencies faced by Sinar Bulan Bintang. Sinar Bulan Bintang is one of the MSMEs in Batam that operates as a minimarket. This business has been running for 18 years and during that time the owner recorded receipts and expenses manually and even making estimates based on memory. As a result, partners experience difficulties recording and bookkeeping, which results in inaccurate decisions. Therefore, the right solution to deal with this problem is to design a computerized accounting recording system through Microsoft Access. The method of collecting data is by interviewing, observing, and documenting the owners and members of Sinar Bulan Bintang. The results of this research are in the form of a system designed with Microsoft Access and available various features needed by partners. One of these features also involves generating financial reports in the form of income statements, balance sheets, capital reports, trial balance reports, and sales reports. This system allows owners and partners to make more accurate and informed decisions during their daily operations.